Acute effects of electrostimulation and blood flow restriction on muscle thickness and fatigue in the lower body - Santiago-Pescador, S.; Fajardo-Blanco, D.; López-Ortiz, S.; Peñín-Grandes, S.; Méndez-Sánchez, R.; Lucia, A.; Martín-Hernández, J.; Santos-Lozano, A. (European Journal of Sport Science, 2022)
Neuromuscular electrical stimulation (NMES) in combination with blood flow restriction (BFR) enhances muscle hypertrophy and force-generating capacity. The present study aimed to investigate the acute effects of BFR and NMES, both in isolation and in combination, on muscle thickness (MT) and fatigue in the lower body of 20 young healthy subjects. Different stimuli were applied for 25 min, defined by the combination of BFR with high- and low-frequency NMES, and also isolated BFR or NMES. Changes in MT were then evaluated by ultrasound of the rectus femoris (RF) and vastus lateralis (VL) muscles at the end of the session (POST) and 15 min later (POST 15`). Lower limb fatigue was evaluated indirectly by strength performance. Results showed that RF MT was higher under the combined protocol (BFR + NMES) or isolated BFR than under NMES - regardless of the frequency - both at POST (p = 0.018) and POST 15` (p = 0.016). No significant changes in MT were observed under isolated NMES or BFR at POST 15` when compared with basal values (p = 0.067). No significant differences were observed for VL MT between conditions (p = 0.322) or for fatigue between conditions (p = 0.258). Our results indicate that a combination of BFR and NMES acutely increases MT in sedentary subjects. Also, although not significantly, BFR conditions had a greater tendency to induce fatigue than isolated NMES.